Mass migration and seasonality: evidence on Moldova's labour exodus - Dennis Görlich; Christoph Trebesch (Kiel Institute for the World Economy (IfW), 2006)
This paper identifies the determinants and patterns of mass migration in Moldova a country in which migration has become the dominant socioeconomic phenomenon in a period of less than 8 years. Special emphasis is placed on seasonal migration, which has become increasingly popular in many Eastern European countries. Our findings indicate that poverty is a main push factor of migration decisions. Additionally, network effects and migration experience appear to be crucial for Moldovan migration flows. Concerning the choice of seasonal vs. permanent migration, we find that neither young dependents in the household nor marital status seem to influence the migrant's decision of whether to leave seasonally or permanently. The main group of seasonal migrants are less educated men from rural areas.
Keywords: 330